Cultural Dissonance in Piano Pedagogy in Post-Colonial China - Zhang, Fengyi (Chopin Review, 2023)
The popularity of the piano in China grew steadily through the 1980s. Many popular piano tutor books in today’s China stem from the Western world, and they are often several decades old, but re-published in Chinese versions. However, their use exposes significant cultural differences between the West and China. In this article, I will first introduce some historical commentary on the piano and piano pedagogy in China to provide a general background. Then, I will discuss several obstacles to the transmission of piano techniques and interpretation, including issues concerning cultural literacy, the conceptual space between Western metaphorical[1]kinaesthetic teaching methods and Chinese direct verbal instruction, and the difficulties posed by translation. Finally, some discussion of orientalism, prejudice and assimilation will be presented to explore the power relations and ideology that may lie behind these difficulties in transmission. Western piano tutor books used in China, particularly those originating in the mid[1]twentieth century, often feature stylised oriental elements in an attempt to introduce diverse musics from different parts of the world. Yet the accompanying descriptions indicate that this introduces explicit and implicit prejudice, and in ways that (ironically) infect even some piano tutor books written by Chinese musicians, thus unwittingly extending and naturalising a system of global cultural hegemony. When we consider that these are beginner tutor books used by children of primary school age, the long[1]term effects of this musical orientalism come into focus: although superficially China has striven toward cultural autonomy, thanks to these teaching materials, Western hegemonic views of Chinese music may remain current and are indeed internalised by Chinese musicians.